Particle Methods for Viscous Flows: Analogies and Differences Between the SPH and DVH Methods (Communications in Computational Physics, 2018)
In this work two particle methods are studied in the context of viscousflows. The first one is a Vortex Particle Method, called Diffused Vortex Hydrodynamics(DVH), recently developed to simulate complex viscous flows at medium and highReynolds regimes. This method presents some similarities with the SPH model andits Lagrangian meshless nature, even if it is based on a different numerical approach.Advantages and drawbacks of the two methods have been previously studied in Colagrossiet al. [1] from a theoretical point of view and in Rossi et al. [2], where theseparticle methods have been tested on selected benchmarks. Further investigations arepresented in this article highlighting analogies and differences between the two particlemodels.